2013
DOI: 10.1002/ijc.28520
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblasts might sustain the stemness of scirrhous gastric cancer cells via transforming growth factor-β signaling

Abstract: Cancer-associated fibroblasts (CAFs) have recently been implicated in tumor growth and metastasis in gastric cancer. Cancer stem cells (CSCs) have been proposed to have an important role in cancer progression. The aim of this study was to clarify the effect of CAFs on CSCs characteristics in gastric carcinoma. Scirrhous gastric cancer cell lines, OCUM-12 and OCUM-2MD3, and non-scirrhous gastric cancer cell lines, MKN-45 and MKN-74, were used. OCUM-12=side population (SP) cells and OCUM-2MD3=SP cells were sorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 26 publications
3
87
0
Order By: Relevance
“…1F). Many studies have reported the critical role played by cancer associated fibroblasts in the metabolism of the tumour via growth factor signalling (Chen et al, 2014;Hasegawa et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…1F). Many studies have reported the critical role played by cancer associated fibroblasts in the metabolism of the tumour via growth factor signalling (Chen et al, 2014;Hasegawa et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The role of the LOX family is widely accepted as a poor prognosis factor for patients with several kinds of cancer [5][6][7][8][9], while comparatively few papers examined tumor-suppressive roles of the LOX family in bladder and lung cancers [10,11]. It has been reported that transforming growth factor β (TGFβ) plays an important role in various aspects of the metastatic spread of cancer cells, such as migration, invasion, and epithelial-mesenchymal transition, via autocrine or paracrine manner [12][13][14][15][16]. We previously reported that LOX and LOXL2 expressions are associated with gastric cancer progression [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of CAFs was significantly inhibited by TGF-b inhibitors, but not by fibroblast growth factor receptor or cMet inhibitors. These findings suggest that CAFs might promote CSC properties in scirrhous GC through TGF-b signaling [44] . IL-17B induced the expression of the self-renewal-related genes Nanog, Sox2, and Oct4 in mesenchymal stem cells and promoted tumor progression.…”
Section: Gcsc Regulation In the Tumor Microenvironmentmentioning
confidence: 80%